The Role of Leadership Influencing the Health Equality Through Urban Design in the City of Surabaya, Indonesia - Ibnul Haqi, Faruq; Pieters, Johannes (International Journal of Engineering and Technology, 2019)
The World Health Organisation (WHO) has advocated a key role for local government in the struggle to improve health equality in developing countries. The Indonesian government has developed its own model of local government intervention for addressing health and wellbeing among citizens known as Kota Sehat program. Additionally the governments prioritise on urban health is very much a function of socio-cultural norms and leadership styles. The role of political leadership is therefore particularly important regarding local government interventions to promote health equality. Urban design is one of a number of factors in the built environment which have been shown to be important in promoting physical activity and social interaction which in turn are important mediators of physical and mental health. The challenges for policy makers in Indonesia regarding sustainability and health in cities has been stressed in particular the development of urban design principles especially in the City of Surabaya. The research established a theoretical framework for urban design protocols such as productivity, liveable, sustainability, design excellence and leadership. The aim of this study was to examine the extent to which the administration of the City of Surabaya is improving public health and creating a healthy and sustainable city. The findings indicate that the quality of mayoral leadership has played a vital role in enhancing the quality of urban life in Surabaya. The mechanisms underlying this role include that the mayor has a sound understanding of urban design and has been able to intervene to insist on good urban design as urban policy.Â Â